APPLICATION OF VOLATILE FRACTIONS FROM AGERATUM HOUSTONIANUM AND TAGETES ERECTA AS SAFE MANAGEMENT OF SOME ROOT PHYTOPATOGENIC FUNGI - K Ramadan; M Ali; R El-Gobashy; P Georghiou; N Ali; E Zaher (Arab Universities Journal of Agricultural Sciences, 2007)
Ageratum houstonianum Mill and Tagetes erecta L. (Asteraceae) were subjected to hydrodis-tillation as well as the stepwise extraction with organic solvents. Crude extracts and the hydrodis-tilled essential oils (E.O) were bioevaluated against two phytopathogenic fungi Rhizoctonia solani and Phytophthora megasperma in vitro. The volatile fraction from both plants showed a good antifungal activity towards the tested fungi, EC50s were 91 and 1369 ppm for R. solani and 84 and 1571 ppm for P. megasperma with Ageratum essential oil (E.O) and Tagetes E.O, respectively. But generally; Ageratum E.O was found to be more effective in reducing mycelium growth of R. solani and P. megasperma (EC50 = 91 and 84 ppm respectively) than Tagetes E.O. Chemical compo-sition of Tagetes E.O and Ageratum E.O; fractions F1 (solid) and F2 (liquid) fractions were investi-gated by GC-MS analysis. Interestingly, heterocy-clic benzopyrane compound (Precocene II) was only component which has been detected in Ager-atum E.O fraction F1. Precocene II seems to be the fungitoxic active components in Ageratum E.O and its fractions. However, monoterpenic hydro-carbons were correlated with the fungitoxic effect of Tagetes E.O. In the green house experiments, Tagetes E.O and Ageratum E.O fraction F1 showed a clear selectivity towards tested patho-gens; Rhizoctonia solanii and Phytophthora megasperma. Ageratum E.O; fractions F1 was found to be much more fungitoxic activity than Tagetes E.O. Tagetes E.O and Ageratum E.O frac-tions F1 were controlled the 90.91% of Root-Rot disease in bean caused by Phytophthora megasperma, while the percentage of disease con-trol was only 36.36% for Rhizoctonia solani.